Onde and envy: A diachronic cognitive approach - Hebda, Anna (Społeczna Wyższa Szkoła Przedsiębiorczości i Zarządzania w Warszawie, 2010)
The present paper offers a comparative analysis of a native Middle English emotion term onde < OE anda and its French-derived counterpart envy from the point of view of diachronic cognitive linguistics. The contextual analysis of the lexemes in question has been conducted on the basis of data from the Middle English part of The Helsinki corpus of English texts: Diachronic and dialectal and a selection of 41 Middle English texts representing different dialect continua. It is claimed that the overlap in the conceptualisation of the lexemes in question contributed to the expansion of the loan at the expense of the native term. The design of the study follows that of Fabiszak – Hebda (2007).
Keywords: Middle English; onde; envy; diachronic emotionology; emotion talk; Conceptual Metaphor Theory